1992
DOI: 10.1002/j.1460-2075.1992.tb05067.x
|View full text |Cite
|
Sign up to set email alerts
|

Dtrk, a Drosophila gene related to the trk family of neurotrophin receptors, encodes a novel class of neural cell adhesion molecule.

Abstract: We report the identification and molecular characterization of Dtrk, a Drosophila gene encoding a receptor tyrosine kinase highly related to the trk family of mammalian neurotrophin receptors. The product of the Dtrk gene, gp160Dtrk, is dynamically expressed during Drosophila embryogenesis in several areas of the developing nervous system, including neurons and fasciculating axons. gp160Dtrk has structural homology with neural cell adhesion molecules of the immunoglobulin superfamily and promotes cell adhesion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
95
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(101 citation statements)
references
References 70 publications
6
95
0
Order By: Relevance
“…S2 insect cells overexpressing Ark formed multicellular aggregates that could be blocked by excess recombinant Ark ECD (6). Similar results could be achieved upon overexpression of D-Trk or protein phosphatase-and -in the same S2 cells (7)(8)(9). These data raise the possibility that receptor tyrosine kinases and transmembrane phosphatases may function both as adhesion molecules and as elements of the signaling cascade.…”
supporting
confidence: 62%
“…S2 insect cells overexpressing Ark formed multicellular aggregates that could be blocked by excess recombinant Ark ECD (6). Similar results could be achieved upon overexpression of D-Trk or protein phosphatase-and -in the same S2 cells (7)(8)(9). These data raise the possibility that receptor tyrosine kinases and transmembrane phosphatases may function both as adhesion molecules and as elements of the signaling cascade.…”
supporting
confidence: 62%
“…MT1-MMP directly cleaves the PKP 621 2LI sequence in an exposed region of PTK7, generating the N-terminal, soluble PTK7 ectodomain. Because PTK7 readily oligomerizes through its ectodomain (10,52), membrane PTK7 forms a complex either with itself or with the solubilized ectodomain or with some yet to be identified adaptor protein(s) (2, 13, 39 -41, 43, 48). It is likely that these different complex types elicit the dissimilar downstream signaling events and that these signaling events differentially regulate multiple cell functions, including PCP and directional motility, in processes as diverse as cancer cell invasion and embryonic cell migration during gastrulation in eukaryotes (13,18,28,30).…”
Section: Discussionmentioning
confidence: 99%
“…Drosophila trk homologue promotes cell adhesion by homophilic interaction of the extracellular domains (Pulido et al, 1992). Tannahill et al (1995) have demonstrated that coating of cell culture dishes with trkA ectodomain inhibits neurite outgrowth, indicating that this domain in¯uences neuronal adhesion.…”
Section: Discussionmentioning
confidence: 99%